Assessing the net overall distributive effect of a congestion charge - Jillian Anable; Phil Goodwin (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper offers new insights into the definition, measurement and operationalisation of different dimensions of social vulnerability to road user charges, using unique data sets available in the UK. Assessing distributional effects of road pricing or congestion charging schemes requires evaluating distributional patterns: who receives the benefits of reduced congestion and who receives the revenues collected? How these impacts change over time also needs consideration.
Keywords: 330